Fatigue life enhancement for friction stir welded AA6061 butt joint through high frequency mechanical impact (HFMI) of pneumatic impact treatment (PIT) / Mohamed Ackiel Mohamed - Mohamed, Mohamed Ackiel (Institute of Graduate Studies, UiTM, 2017)
The welding and joining industry in the past few decades has witnessed a huge growth in pursuit of process optimization and design minimization due to the continued escalation of prices. A relatively typical new welding process that requires wide attention in process optimization for an ideal low defect joint and life cycle improvement is friction stir welding due to its advantage of having minimal parameters to be controlled during the process. However, despite its many advantages tensile residual stress in friction stir welded joints remains to be a significant concern due to its extensive clamping and stirring process causing a lower fatigue resistance particularly in structures subjected to fluctuating loads triggering a need for improvement by utilizing modern post-weld treatment processes. Aiming to apply the HFMI method of pneumatic impact treatment (PIT) to enhance the fatigue performance of a 6 mm thick AA6061-T651 FSW butt joint, this research consisted of three main phases. The initial phase focused on the optimization of the rotational and traverse speed based on multiple mechanical properties and quality features, which emphasized on the tensile strength, hardness and the weld quality class using the Multiobjective Taguchi Method (MTM). Furthermore, the first order model for predicting the mechanical properties and weld quality class was derived by applying Response Surface Methodology (RSM).